2016
DOI: 10.1002/2016gl068416
|View full text |Cite
|
Sign up to set email alerts
|

Controls on and effects of armoring and vertical sorting in aeolian dune fields: A numerical simulation study

Abstract: Unlike ripples, there are only few numerical studies on grain size segregation at the scale of dunes in aeolian environments. Here we use a cellular automaton model to analyze vertical sorting in granular mixtures under steady unidirectional flow conditions. We investigate the feedbacks between dune growth and the segregation mechanisms by varying the size of coarse grains and their proportion within the bed. We systematically observe the development of a horizontal layer of coarse grains at the top of which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…While it may seem that an immobility threshold of 5% is small, this value is comparable to the results reported by Gao et al. (), who found that aeolian dunes do not form when the initial proportion of coarse (i.e. immobile) grains within the bed is greater than 4–5%.…”
Section: Discussionsupporting
confidence: 87%
“…While it may seem that an immobility threshold of 5% is small, this value is comparable to the results reported by Gao et al. (), who found that aeolian dunes do not form when the initial proportion of coarse (i.e. immobile) grains within the bed is greater than 4–5%.…”
Section: Discussionsupporting
confidence: 87%
“…Desert landscapes with abundant sand supply and a wide grain-size distribution often exhibit evidence of vertical grain sorting, suggesting that armor layers should be present in most arid landscapes, as confirmed by recent field observations (Gao et al, 2016). Armor layers in natural landscapes can vary greatly in depth and typically become thicker near the ripple crest but can be as thin as a monolayer at the surface (Bagnold, 1941;Sharp, 1963).…”
Section: Introductionmentioning
confidence: 55%
“…Other studies have suggested that changes in surface roughness and saltation threshold can lead to the development of armor layers at the surface in the presence of saltating particles (Rasmussen and Sørensen, 1999;Gao et al, 2016). At values of u * > 0.55 m s -1 , the flux density of particles ranging in size from 0.125 to 0.25 mm remained fairly constant or decreased slightly at the measurement height of 0.185 m. These trends were only observed for the smallest size fraction when shear velocities were large.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations